Clinical outcomes and prognostic factors of adult’s Ewing sarcoma family of tumors: single center experience - Uyeturk, Ummugul; Helvaci, Kaan; Demirci, Ayse; Sonmez, Ozlem Uysal; Turker, Ibrahim; Afsar, Cigdem Usul; Budakoglu, Burcin; Arslan, Ulku Yalcintas; Oksuzoglu, Omur Berna; Zengin, Nurullah (Contemporary Oncology/Współczesna Onkologia, 2016)
Aim of the study was to investigate the demographics of Ewing sarcoma family of tumours (ESTF) patients, treatment alternatives, clinical outcomes, and prognostic factors for survival. Material and methods : We retrospectively reviewed 39 patients with ESFT who were admitted to our institute between September 2008 and September 2012. Results: The patients included 32 (82.1%) males and seven (17.9%) females of median age 24 (range, 18–66) years. Among the 27 patients with a primary osseous localization, 17 (43.5%) had a central axis localization. Fifteen patients (38.5%) had metastases at the time of diagnosis. Patients were followed up for a median period of 18 (range, 2–134) months. The median event-free survival (EFS) was 23 (range, 1–64) months, and the 1- and 4-year EFS were 60% and 48%, respectively. The median overall survival (OS) was 91 (range, 1–188) months, and the 1- and 4-year OS were 78% and 54%, respectively. Gender, age, primary tumor site, and local treatment modalities, either alone or in combination, did not have a significant effect on OS (p = 0.210, p = 0.617, p = 0.644, and p = 0.417, respectively). In contrast, osseous site of peripheral localization, limited stage, and metastasis to the bone significantly affected OS (p = 0.015, p < 0.001, and p = 0.042, respectively). Discussion : ESFTs are aggressive tumors with a high rate of relapse and metastatic potential. Patients with peripheral bone involvement and limited stage had a good prognosis. Appropriate surgical resection, radiotherapy, and aggressive chemotherapy regimens are recommended.